Extending the critical force model to approach critical power in tethered swimming, and it relationship to the indices at maximal lactate steady-state - Pessoa Filho, D. M.; Denadai, B. S. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Critical force (Fcrit) was defined as the tether force at full-tethered conditions that could be maintained without fatigue (Ikuta et al, 1996). The purposes were to access tether-power from critical force model (CPTeth), and to compare CPTeth and power at maximal lactate steady state (PTethMLSS), critical velocity (CV) and velocity at MLSS (vMLSS). METHODS: Ten male swimmers (16.6+/-1.4 years, 69.8+/-9.5kg, 175.8+/-4.6cm) were submitted to the measurements of the CPTeth (plotting impulse against time by linear and non-linear two parameters equation), CV (linear adjustment between time and velocity performance in the 200, 400 and 800-m), PTethMLSS (3 or 4 trials ranging from 95 to 105% of non-linear Fcrit), and vMLSS (3 or 4 trials ranging 85-95% of the 400-m crawl performance). A range of 75-100% of the active drag force (Fr) was applied to manager load in the full-tethered swimming conditions. Fr was evaluated according Toussaint et al. (1998). The MLSS was considered the greatest fractions that did not elicit a lactate accumulation above 1mmol/L between 10th and 30th minutes. The measure of CPTeth and PTethMLSS was approached to the tether force equation times hydrofoil velocity. Pearson's coefficient did correlate the variables, and the difference between two means was checked by paired t-test. Significance was set at p . 0.05. RESULTS: The slope of tether-force vs. time adjustments given a mean value (5.63+/-0.80kg) closed to that (6.87+/-1.02kg) reported to Ikuta et al. (1996). But, neither CV (1,195+/-0,116m(s) nor the CPTeth (98.49+/-21.63W) or Fcrit (55.14+/-7.82N) matches the statements for MLSS, once differences were observed to the vMLSS (1.174+/-0.109m/s), PTethMLSS (89.21+/-15.11W) and force (51.74+/-5.63N) at MLSS, respectively. A strong positive relationship was observed between all endurance variables. DISCUSSION: The steady-load/time to exhaustion model in tethered swimming provided a reliable way to estimate CPTeth, and thus modelling critical power. Despite the good relationship between all variables, the interchangeable use of them seems unreliable.